2022
DOI: 10.18267/j.pep.806
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in Exchange Rate Pass-through in Turkey: A Threshold VAR Analysis

Abstract: This paper analyses the asymmetric behaviour of exchange rate pass-through in Turkey using a threshold VAR model. The main purpose is to examine the asymmetries in the exchange rate pass-through based on size, direction and inflationary environment of an emerging market economy with a highly depreciated domestic currency and two-digit inflation rate. Monthly exchange rate movements and monthly inflation rates were used as threshold variables. Nonlinear impulse response functions were employed to compare upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…A study by Türel & Orhan (2022) found that inflation positively contributes to the currency, but interest rates negatively affect the currency. This finding contradicts research conducted by Alawiyah et al (2019) and Algifari & Rohman (2022) which shows that interest rates have a significant and beneficial influence on foreign exchange rates, while inflation has a negligible negative impact.…”
Section: Figure 1 Average Exchange Rate (Rupiah-usd)mentioning
confidence: 99%
“…A study by Türel & Orhan (2022) found that inflation positively contributes to the currency, but interest rates negatively affect the currency. This finding contradicts research conducted by Alawiyah et al (2019) and Algifari & Rohman (2022) which shows that interest rates have a significant and beneficial influence on foreign exchange rates, while inflation has a negligible negative impact.…”
Section: Figure 1 Average Exchange Rate (Rupiah-usd)mentioning
confidence: 99%